Evaluation of the relationship between adversity quotient, professional identity, and perceived humanistic care of head nurses in Master’s Degrees in nursings - Cai Haina; Gu Lingna; He Qingqing; Wang Yang; Cai Zejun; Tian Chuan; Xu Qinghong (Journal of Family Medicine and Primary Care)
Background: High-level nursing talents play an important role in solving nursing scientific problems and leading nursing innovation, so the construction of high-level nursing talents has become a necessary guarantee for the health strategy in the new era. Managers have high expectations for master’s degree in nursing, hoping that they will develop in all aspects of research, teaching, and professionalism, etc. However, the high expectations of managers have led to unclear job orientation, high clinical and scientific research pressure, and low recognition of nurses’ sense of professional value from the outside world, which have led to the lowering of master’s degree of professional identity and the tendency to leave the profession, which is not conducive to the stabilization of the nursing workforce. Purpose: To explore the influence of adversity quotient, perceived humanistic care of nurse leaders on professional identity of nursing masters, and to clarify the relationship model between the three. Methods: A convenience sampling method was used to conduct an online questionnaire survey on 160 master’s degree nursing students in Ningbo and Shanghai from July to September 2022 using the general information questionnaire, adversity quotient, career identity and perceived humanistic care of nurse leaders scale. Results: Adversity quotient, occupational identity and perceived humanistic care of nurse leaders were all at a moderate level. Adversity quotient (r = 0.430, P < 0.01), perceived humanistic care of nurse leaders (r = 0.443, P < 0.01) and occupational identity were positively correlated, and perceived humanistic care of nurse leaders could affect occupational identity through the mediating effect of adversity quotient, with the mediating effect accounting for 31.8%. Conclusion: Nursing managers should create a good organizational atmosphere, build a training system for adversity quotient courses, conduct regular assessment and humanistic care to improve the ability of nursing masters to face adversity and enhance the awareness of their own professional values.